Integrating depression and acute coronary syndrome care in low resource hospitals in China: the I-CARE randomised clinical trialResearch in context - Yangfeng Wu; Xin Yu; Yidan Zhu; Chuan Shi; Xian Li; Ronghuan Jiang; Sheng Niu; Pei Gao; Shenshen Li; Lijing Yan; Pallab K. Maulik; Guifang Guo; et al. (Elsevier, 2024)
Summary: Background: Acute coronary syndrome (ACS) often co-occurs with depression, which adversely affects prognosis and increases medical costs, but effective treatment models are lacking, particularly in low-resource settings. This study aims to determine the effectiveness of an ACS and depression integrative care (IC) model compared to usual care (UC) in improving depression symptoms and other health outcomes among patients discharged for ACS in Chinese rural hospitals. Methods: A multicentre, randomised controlled trial was conducted in sixteen rural county hospitals in China, from October 2014 to March 2017, to recruit consecutively all ACS patients aged 21 years and older after the disease stablised and before discharge. Patients were randomly assigned in a 1:1 ratio to receive either the IC or UC, stratified by hospital and depression severity. Patients allocated to IC received an ACS secondary prevention program and depression care including case screening, group counselling, and individual problem-solving therapy. Patients allocated to UC received usual care. The primary outcome was change in Patient Health Questionnaire-9 (PHQ-9) from baseline to 6 and 12 months. Main secondary outcomes included major adverse events (MAEs) composed of all-cause death, non-fatal myocardial infarction and stroke, and all-cause re-hospitalisation. Participants were followed up till March 2018. All data were collected in person by trained assessors blinded to treatment group and MAEs were adjudicated centrally. This trial is registered with ClinicalTrials.gov, NCT02195193. Findings: Among 4041 eligible patients (IC: 2051; UC: 1990), the mean age was 61 ± 10 years and 63% were men. The mean PHQ-9 score lowered at both 6 and 12 months in both groups but was not lower in IC compared to UC at 6 months (mean difference (MD): −0.04, 95% confidence interval (CI): −0.20, 0.11) or 12 months (MD: −0.06, 95% CI: −0.21, 0.09). There were no treatment group differences for MAEs or other secondary outcomes except for secondary prevention medications at 12 months (45.2% in IC vs 40.8% in UC; relative risk: 1.21, 95% CI: 1.05-1.40). Pre-specified subgroup analyses showed that IC, compared to UC, may be more effective in lowering PHQ-9 scores in women, older patients, and patients with low social support, but less effective in moderately and severely depressed patients (all p for interaction <0.05). Interpretation: The study found that the cardiology nurse-led ACS- and depression-integrated care, compared to usual care, did not improve depression symptoms in all patients discharged with ACS. Greater benefits in certain subgroups warrants further studies. Funding: R01MH100332 National Institute of Mental Health.